2022
DOI: 10.3390/educsci12040281
|View full text |Cite
|
Sign up to set email alerts
|

Design, Development, and Evaluation of a Virtual Reality Serious Game for School Fire Preparedness Training

Abstract: Immersive virtual reality (VR) is a technology that can be effective for procedural skills training through game-based simulations such as serious games. The current study describes the instructional design, development, and evaluation of the FSCHOOL fire preparedness serious game in a cave automatic virtual environment (CAVE-VR) for elementary school teachers. The main game mechanics include a storytelling scenario, enhanced realism, freedom of movement, levels, and points corresponding to the learning mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The cutting edge of immersive VR technology uses head-mounted displays to create the sense of occlusion and separate the human senses from the physical environment that takes full control of them. Moreover, there are room-size VR applications based on 3D projection mapping, similar to the CAVE TM technology from the 1990s, that can enable complex simulations with specialized real equipment and devices in a multi-person, high-resolution 3D video and audio environment [29]. AR operates in our physical surroundings by overlaying digital elements and objects that are visible through smart, wearable, see-through devices such as head mounted displays, glasses, mobile phones, glass windows, and car windshields [30].…”
Section: Digital Immersive Technologiesmentioning
confidence: 99%
“…The cutting edge of immersive VR technology uses head-mounted displays to create the sense of occlusion and separate the human senses from the physical environment that takes full control of them. Moreover, there are room-size VR applications based on 3D projection mapping, similar to the CAVE TM technology from the 1990s, that can enable complex simulations with specialized real equipment and devices in a multi-person, high-resolution 3D video and audio environment [29]. AR operates in our physical surroundings by overlaying digital elements and objects that are visible through smart, wearable, see-through devices such as head mounted displays, glasses, mobile phones, glass windows, and car windshields [30].…”
Section: Digital Immersive Technologiesmentioning
confidence: 99%
“… 37 In addition, VR simulation is appropriate for disaster preparedness training, providing challenge, enjoyment, and mastery. 52 The VR can benefit more areas in the training system as fire evacuation, especially in overcrowded places. That is due to the cost of fire evacuation drills in such places and the tendency for accidents to occur during the emergency response.…”
Section: Discussionmentioning
confidence: 99%
“…For example, unlike strategy games, shooting games (like FPS) require different cognitive demands and different strategies. Different studies have shown that virtual reality design an interactive environment, increasing the participation and motivation of students and providing deeper learning [10].…”
Section: B Locomotionmentioning
confidence: 99%